Undergraduate Students’ Attitude Towards Learning English: A case Study at Nong Lam University - Viet, Vo Van (VNU Journal of Science: Education Research, 2017)
Effective learning a second language is influenced by many factors. Among of those, attitude has been identified as an important one. Better understanding of students' attitude will help language teaching programmers, school managers and educators to develop strategies to improved student’s learning outcomes. The drive of this study is to explore students’ attitude toward learning English. Data were collected through a questionnaire from a total of 694 students at Nong Lam University. The results of the study showed that the students have positive attitude toward learning English as a foreign language.